Finance for development : Latin America in comparative perspective - Stallings, Barbara (Brookings Institution Press, 2006)
"Access to finance is a critical element in any effort to promote development in emerging market economies. In this analysis of the Latin American financial sector, Barbara Stallings and Rogerio Studart examine recent transformations in the region, compare them to related developments elsewhere, and consider where they might lead. They challenge the new literature on finance and development, which argues for the elimination of public-sector banks, substitution of private monitoring for government regulation and supervision, and more complete integration with international capital markets. Rather, the authors advocate a more balanced approach that emphasizes individual country situation and strengthens the institutional context in which financial systems operate." "Case studies illustrate changes occurring in Chile, Mexico, and Brazil - the most sophisticated financial systems in Latin America. The authors place particular emphasis on the need to overcome two types of market failure: the lack of long-term finance for investment and access to credit for small firms. They conclude with policy recommendations for strengthening Latin American banks and capital markets so that they can play a greater role in supporting economic development."--Jacket